Neural innervation stimulates splenic TFF2 to arrest myeloid cell expansion and cancer - Zina Dubeykovskaya (Nature Portfolio, 2016)
During colorectal inflammation and cancer, myeloid cells accumulate in the spleen and suppress the host immunity response. In this study, the authors use a mouse model of colitis to demonstrate that upon vagus stimulation splenic memory T cells release TFF2, which suppresses the expansion of myeloid cells and cancer progression.